Media Markets with Habit Formation - Ralf Dewenter (Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2003)
The aim of this paper is to analyse the pricing behaviour of print media firms when consumption on reader markets is addictive or habituated. However,not only the reader but also the advertising market has to be considered by a publisher optimising profits.Because print media markets are highly concentrated a monopoly-monopoly model is built,where both markets are of monopolistic structure.Moreover,a monopoly-duopoly model is considered,where only the reader market is monopolistic but the advertising market is of duopolistic structure.To compare the results from the models regarding habit effects,simple static models are presented as a benchmark.
urn:nbn:de:gbv:705-opus-1332
Keywords: 330; Zeitungsverlag; Zeitschriftenverlag; Betriebliche Preispolitik; Medienverhalten; Konsumentenverhalten; Zeitungswerbung; Duopol; Theorie; Gewohnheit